More Than Lip Service Is Needed - Herman, Al (Canadian Journal of Counselling and Psychotherapy, 1972)
One hundred and forty-four students from grades four, five, and six were asked to write paragraphs describing their vocational plans. Six judges classified the paragraphs according to Ginzberg's stages of vocational development. Results showed that certain characteristics are functional in decision-making processes earlier in life than had been hypothesized by Ginzberg, indicating the desirability for provision of information concerning vocations and the world of work at the elementary school level. Advancement through the stages correlated positively with age and grade. Maturity of choice correlated with the female sex. Intelligence had no significant bearing upon Ginzberg's stages of development of youth.